Cyclic behavior of a two-span RC beam built with plain reinforcing bars - Fernandes, Catarina (2011)
Reinforced concrete structural elements lacking appropriate seismic detailing and built with plain reinforcing bars, and subjected to cyclic loads like the ones induced by earthquakes, are particularly sensitive to the bond-slip mechanism. Though, existing studies on the cyclic behavior of RC structures generally refer to elements with deformed bars. As a result, the behavior of elements with plain bars is not yet fully understood. In this framework, the cyclic behavior of a two-span RC beam built with plain reinforcing bars, collected from an ancient building structure, was investigated. The support and loading conditions observed in-situ were simulated in the test setup. The beam displayed a flexural failure and the damage was concentrated in three short plastic hinges. The poor damage distribution evidences the effects of the bar slippage mechanism on the beam behavior